Adieu, de Balzac : « Une absence au monde qui vient de se déclarer au cœur de l’histoire » - France Vernier (Amnis)
The fate of many “forgotten” victims of the Napoleonic campagnes was never far from Balzac’s literary concerns, and in addition to Le Colonel Chabert, one can find throughout his work various examples of soldiers of the old guard, either maimed or barely surviving on a meagre pension. There is, however, a less known short story, Adieu, which subject displays an astonishingly modern preoccupation, quite unusual for the period, obliging the author to invent a strange new narrative device, which I believe Balzac borrowed from the then recently discovered psychiatric practice implemented by Esquirol. It is about a woman – quite something –, who has been traumatized by the horrors of the retreat from Beresina (where she had accompanied her husband) and who, after years of wandering, has gone mad and lost her ability to speak. No medical treatment seems able to cure her. The short story, which takes on the unbelievable challenge of introducing the reader into the universe of an aphasic madwoman, evokes the spectacular strategy her one time lover invents in order to momentarily revive her sanity and her powers of speech, before her death and his suicide ten years later. The reader in turn is stimulated to an ever deeper reflection on the fate of this “collateral” victim, and the effect Balzac’s text has on a re-focusing of History.